Visual Cryptography Based Authentication For Parallel Network File Systems - Keerthivasan, R; Srivastavan Iyer, KS; Vyshnav, AK; Vishal, M (International Journal of Computer Sciences and Engineering, 2025)
The problem of securing multiple communications in large-scale network files systems supporting parallel access to multiple storage devices. That is, we consider a model of communication where there are a high number of clients accessing multiple remote and distributed storage devices in parallel. Particularly, focusing on exchange key materials and establishing secure parallel sessions between the clients and the storage devices in the parallel Network File System (pNFS) the current Internet standard is in an scalable and efficient manner. The development of pNFS is driven by Netapp, Panasas, Sun, EMC, IBM, and UMich/CITI, and thus it shares many common features and is compatible with many existing commercial/proprietary network file systems. Networking is considered as the practice of linking multiple computing devices together for sharing of resources. Without the implementation of network, businesses, government agencies, and schools would be unable to operate as efficiently as they do. An organization is able to connect dozens of computers to a single printer is a seemingly simple, yet extremely useful capability. Perhaps even more valuable is the ability to access the same data files from various devices throughout a building. This is incredibly useful for companies that may have files that require access by various employees daily. By the use of network, a same file is made available to several employees on separate computers simultaneously, which improves the efficiency of the organization. Our objective is to implement visual cryptography for strong authentication for parallel network file systems.